The Implementation of Socioeconomic Well-Being of Waqf and Properties in Muhammadiyah Regional Board Yogyakarta - Akhmad Affandi Mahfudz; Syamsuri Syamsuri; Anisa Rosdiana Zein; Isma Aulia Roslan; Nurmagambetova Azhar Zeinullayevn (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
Waqf is one of the financial instruments that can improve the socioeconomic status of Ummah. However, the number of waqf assets exceeds expectations due to a lack of proper management. The socioeconomic well-being of the Ummah is among the core principles of waqf management in the form of accountability and transparency. This study aims to unveil the implementation of the Socioeconomic well-being of Waqf Board Management, taking the case of the Muhammadiyah Waqf Council in Yogyakarta, Indonesia. This research employs descriptive analysis through structured interviews, passive participation observation, and documentation. The study found that the principles of socio-economics well-being have been implemented by the Waqf Board Management of Muhammadiyah Yogyakarta in the form of accountability, including compliance and Integrity, Administration, Programs, Practice, and Finance. The principle of transparency includes the level of openness in the delivery of public services, ease of understanding of the rules and procedures for providing services, and the availability of information on various fields of public administration. This paper implies the massive policy direction of Waqf Board Management among the Muhammadiyah Organization in Indonesia, which is the second largest Muslim organization in the country, to ameliorate the way of implementing the socio-economics of waqf management.